Trends of criticism between the two caliphs: Omar bin Alkhatab and Abdulmalek bin Marwan: A comparative study of environment effect - Hasan, Awadh Ahmed (Arab Journal for Sciences and Research Publishing, 2021)
The study depended to highlight the affection of the environment in the criticism of the two caliphs; Omer bin Al-Khatab and Abdul-Malik bin Marwan, both caliphs depended on the self-rule based on instinct and own view, as their judgments based on reading one verse and their emotions with it, according to their environments and cultures, nevertheless, they provided the Arab criticism by laying the first foundations for some critical standards that were the basis upon which Arab critics relied after them, especially the critics of the fourth century AH, of those standards:- Realistic honesty, go away from strangers and mix words together, division, and the quality of the meaning according to its suitability with Islamic meanings. This is what came out from the criticism of Caliph Omar bin Al-Khattab- As the criticism of caliph Abdul-Malik bin Marwan, it was produced: the need for the poet to take into account the ingenuity of the introduction, the contexts of the praising poem, and identifying the speech as appropriate, and create and generate meanings as renewal in the metaphor, to his credit, he followed the methods of balancing the poets' meanings.
Keywords: Criticism of the Two Caliphs; Influence of the Environment; The Early Islamic Era; The Umayyad Era; The Dilemma